PENGARUH FERMENTASI ALAMI LIMBAH INDUSTRI KALAMANSI TERHADAP PENINGKATAN RENDEMEN DAN MUTU MINYAK ATSIRI - Tuti Tutuarima (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Orange peel oil is stored in the oil glands located on the outer skin. Orange peel contains cellulose, hemicellulose, pectin and other components. Microorganisms can damage the skin layer and are expected to increase oil yield. This study aimed to evaluate the effect of natural fermentation on citrus peel waste on yield and quality of the essential oils produced. This study used natural fermentation time as a treatment factor for 2, 3, and 4 days. The results of this study indicated that the natural fermentation time that occurs in kalamansi peel waste can increase the oil yield. Natural fermentation for 4 days produces the highest yield. This natural fermentation process also does not affect the quality characteristics of the oil.